Dermatological Diseases in a Chepang Community - Niraj Parajuli; Sushil Paudel (Nepal Journal of Dermatology, Venereology & Leprology)
Chepang is an indigenous group residing mostly in the hilly region of central Nepal. They are still considered as most marginalized and socio-economically deprived group in the country. There are just a handful of studies on the health status of this community but none of these studies were dedicated on the dermatological issues. A two-day dermatological outreach camp dedicated for Chepang community was conducted at Makawanpur district of central Nepal. Dermatophyte infections and scabies were the most common dermatological problems noted. The poor socio-economic status, poor hygiene combined with illiteracy was the major factor contributing to these conditions and their overall health.